Indonesian Bank Profitability: Sharia VS Conventional Bank - Sucipto, Rosita Hidayati; Puspita, Rosana Eri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to analyze the differences in profitability of Islamic and conventional banks for the 2018-2022. The data collection method is by documentation on the annual financial statements of Islamic and conventional through the official website of each bank and taking the financial ratios. The sampling technique is purposive, so samples of 10 Islamic banks and 10 conventional banks. The finding that capital adequacy positively and significantly affects profitability in conventional banks, while it does not affect Islamic banks. The level of bank efficiency has a positive and significant effect on conventional and Islamic banks. Liquidity has a positive and significant effect on the profitability of conventional banks and does not have a significant effect on Islamic banks. Based on the results of the comparison of the mean of conventional banks and Islamic banks, it shows that the level of efficiency and liquidity of conventional banks is better than Islamic banks. Meanwhile, capital adequacy in Islamic banks is better than in conventional banks